Teachers' Perception of Children's Behavioral Adjustment in Tanzanian Preprimary Schools and Their Relationship to Teachers' Cultural Beliefs Regarding Obedience, Cooperation, and Play. Issue 1 (January 2015) - Shavega, Theresia Julius; van Tuijl, Cathy; Brugman, Daniel
<x xml:space="preserve">Abstract</x> This article addresses teachers' perception of behavioral adjustment in preprimary school children and how they relate to teachers' cultural beliefs and to the behavioral management strategies used by the teachers. The sample consisted of 120 preprimary teachers from 60 schools in 3 regions of the mainland of Tanzania. Teachers' perception of children's behavioral adjustment and teachers' behavioral management strategies were reported by teachers through interviews, whereas teachers' cultural beliefs were measured by questionnaires. About 70% of the teachers perceived children to display externalizing behaviors in class, which ranged from moderate (13%) to high (60%) proportions of children, and teachers reported applying supportive and restrictive behavioral management strategies to stimulate behavioral adjustment in children. Teachers' use of a restrictive behavioral management strategy was positively related to teachers' perception of children's externalizing behaviors. Furthermore, children in urban schools were perceived to display more externalizing behaviors than children in rural schools. It is argued that current urbanization processes are affecting traditional, collectivist educational strategies in Tanzania. Implications for future research and educational policy are discussed.